Implementasi Strategi Pemasaran Dengan Menggunakan Metode Swot Dalam Upaya Meningkatkan Penjualan Produk Di CV. Maju Djaya Beton - Muhammad Ikhsan; Muhammad Mansur; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2022)
Abstract Companies need to have more effective and efficient strategies so as not to lose consumers to sell their products. CV. Maju Djaya Beton said the company was experiencing several problems related to the marketing of its products. Therefore, several new strategies are needed to further increase the advantages and minimize the disadvantages that have a negative impact on the company. The purpose of this study was to determine the marketing strategy of CV. Maju Djaya Beton using SWOT analysis. This study uses data collection methods directly in the field by means of interviews and observations. Based on the results of the analysis, it can be seen that CV. Maju Djaya Beton is in quadrant I position which is a favorable condition for the company. Opportunities can be obtained by maximizing existing strengths. So it can be concluded that the best strategy that must be applied is to use the Growth Oriented Strategy. Keywords: Marketing Strategy, SWOT Analysis, Sale.